Weight-based Starvation-free Improvised Round-Robin (WSIRR) CPU Scheduling Algorithm - Banerjee, Anuradha; Mondal, Nabajit; Naznin; Basu, Poulomi; Singh, Prateeksha (International Journal of Computer Sciences and Engineering, 2025)
CPU is a primary computer resource, so its scheduling is central to operating system design. When multiple runnable processes exist in the ready queue, OS has the onus of responsibility to decide which one is to run fast. The part of the OS that takes this decision is called scheduler and the algorithm based on which it works, is called the scheduling algorithm. Different kinds of scheduling algorithms exist in the literature. Among them First-Come-First-Served (FCFS), Shortest-job-first (SJF), Priority Scheduling and Round-robin, are mention-worthy. This paper proposes a weight-based starvation-free improvised scheduling algorithm that allocates CPU to processes in round-robin manner while the time quantum is calculated based on the burst time of the processes waiting in the ready queue.